The effect of ice slurry ingestion on perceived thermal stress and fluid intake during a simulated triathlon - Dascombe, B. J.; Stevens, C.; Callister, R.; Sculley, D. V.; Boyko, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The effect of internal pre-cooling strategies prior to exercise has been of research interest in recent times (Siegel and Laursen, 2012), however the efficacy of internal cooling strategies is largely unknown. Perceptions of thermal stress [PTS] and thirst (as measured through voluntary fluid intake [VFI]) assist in the regulation of endurance performance in the heat (Schlader et al. 2011). Therefore, this study investigated the effect of ice slurry ingestion on measures of PTS and VFI during the run leg of a simulated triathlon. Methods: Nine well-trained male triathletes (29.1 ± 3.6 yrs, 61.7 ± 4.7 mL/kg/min, best ODT time: 02:10:37 ± 00:08:32 hr) performed two randomised trials of a simulated triathlon in controlled hot conditions (32-34°C). The triathlon consisted of a paced 1.5 km swim (pool) and 1 hr cycle (ergometer), prior to a self-paced 10 km (treadmill) run. In the middle half of the cycle leg, participants consumed either 10 g/kg BM of ice slurry (ICE) or room temperature (CON) sports drink. Water intake was also allowed ab libitum throughout the cycle leg and at 2 km intervals in the run leg. Physiological and perceptual measures (100mm visual analogue scales) were taken during the cycle and run legs. Paired sample t-tests and two-way repeated-measures analysis of variance with Scheffe post hoc tests were used to determine the effects of ice slurry ingestion. Results: Overall, self-paced 10 km run time significantly improved in the ICE condition (43.4 ± 3.7 vs. 44.6 ± 4 min; P = 0.03). Voluntary fluid intake was significantly (P = 0.03) lower in the ICE (1258 ± 401 mL) compared to the CON (1393 ± 356 mL). PTS was significantly lower at 5 km of the run leg in ICE (73 ± 9 vs. 80 ± 7 mm; P = 0.04) and remained lower throughout the rest of the run leg. Importantly, the 5-10 km split was significantly different between conditions (21.3 ± 1.9 vs. 22.1 ± 2.4 min; P = 0.02). Heart rate, sweat rate, and rating of perceived exertion were similar between conditions. Discussion: These results demonstrate that ice slurry ingestion has a significant effect on triathlon performance, which may be a result of a reduction in the PTS during exercise. Alterations in PTS have been related to the self-selection of exercise intensity, with an increase in PTS having been shown to be related to a decrease in self-selected exercise intensity in the absence of an increased rectal temperature (Schlader et al. 2011). The reduction in VFI in the ICE condition may reflect an anticipatory response to an increase in body heat content (Sawka and Noakes, 2007). As such, the ingestion of ice slurry during endurance exercise appears to be effective in providing both physiological and perceptual thermoregulatory relief.